Elastic crack interaction limit of two interacting edge cracks in finite body - R., Daud; M. A., Rojan; A. K., Ariffin; S., Abdullah (Universiti Malaysia Perlis (UniMAP), 2012)
International Conference on Applications and Design in Mechanical Engineering 2012 (ICADME 2012) organized by School of Mechatronic Engineering, Universiti Malaysia Perlis (UniMAP), 27th - 28th Februari 2012 at Bayview Beach Resort, Penang, Malaysia.